To the question about the culture of intellectual labour of future specialist. (Journal of Educational Sciences, 2016)
In this article the role of culture of intellectual labour is exposed as basis of the professional thinking, showing up in that strategy that must be produced in different situations, in ability to transform these situations in certain problems, and then in the system of searching tasks of certain type. The culture of intellectual labour of future specialist is formed at research component parts of object, phenomenon or process in their action, in connection with an environment and in an image in various and continuously changing actions and counteractions. Therefore the culture of intellectual labour of future specialists requires ability to think, analyse the terms of educational environment. Large attention is spared to independence of reflections about an object, about the phenomenon, about a process as result of reading, conversations and lectures of scientific character, requiring considerable intellectual efforts of finding of truth. The culture of similar intellectual labour requires not only efforts but also certain courage, willingnessto contest the set judgements, if they reflect reality inadequately. Every cultural person needs such courage, expressed in ability not to retreat before the burdens of intellectual labour, honesty of his mind, aspiring to truth at any cost, without the halved decisions and humiliating lie.
Keywords: culture of intellectual labour; independence of reflections; emotional intellect; future specialist.